226k views
3 votes
Which expression is equivalent to 3m + 1 - m?

a. 2 + m - 1 + m
b. 1 + m
c. 3 m - 1
d. 3 m

2 Answers

6 votes

Answer:

Answer is:A

Explanation:

3m + 1 - m = 3m - m + 1

3m - m + 1 = 2m + 1 this is equivalent to 2 + m - 1 + m because

2 + m - 1 + m = m + m + 2 - 1 = 2m + 1

User Dylan B
by
5.0k points
1 vote

Answer:

A

Explanation:

3m+1-m is 2m+1

2+m-1+m is 1+2m

User Ninegrid
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.